Jurgen Habermas : Key Concepts. - Fultner, Barbara (Key concepts., 2014)
A rare systematic thinker, Habermas has furthered our understanding of modernity, social interaction and linguistic practice, societal institutions, rationality, morality, the law, globalization, and the role of religion in multicultural societies. He has helped shape discussions of truth, objectivity, normativity, and the relationship between the human and the natural sciences. This volume provides an accessible and comprehensive conceptual map of Habermas' theoretical framework and its key concepts, including the theory of communicative action, discourse ethics, his social-political philosop.